1998
DOI: 10.1038/sj.hdy.6882700
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for spatial structure and directional gene flow in a population of an aquatic plant, Potamogeton coloratus

Abstract: Six hundred and forty-seven samples of Potamogeton coloratus from 60 ditches in the Gordano Valley, Somerset were analysed for variation at two polymorphic PGM isozyme loci using starch gel electrophoresis. A total of eight genotypes was detected, and a high level of partitioning of genetic variability between ditches was observed with F ST = 0.575. Genetic variability was shown to increase with distance from the head of the valley. The genetic subdivision of the population and pattern of increasing diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 7 publications
1
33
1
Order By: Relevance
“…Hence, hydrochorous dispersal is critical to the maintenance of genetic diversity in macrophyte populations. A number of studies have found that the unidirectional flow of water results in asymmetrical gene flow (Gornall, Hollingsworth, & Preston, ; Pollux et al, ). For instance, Pollux et al () found a significant increase in the genetic diversity of Sparganium emersum populations with distance downstream, gene flow being approximately 3.5 times higher in a downstream direction than upstream.…”
Section: Macrophyte Dispersal and Settlementmentioning
confidence: 99%
“…Hence, hydrochorous dispersal is critical to the maintenance of genetic diversity in macrophyte populations. A number of studies have found that the unidirectional flow of water results in asymmetrical gene flow (Gornall, Hollingsworth, & Preston, ; Pollux et al, ). For instance, Pollux et al () found a significant increase in the genetic diversity of Sparganium emersum populations with distance downstream, gene flow being approximately 3.5 times higher in a downstream direction than upstream.…”
Section: Macrophyte Dispersal and Settlementmentioning
confidence: 99%
“…Previous population genetic studies on riparian plants reported the possibilities of water‐affected dispersal that would result in characteristic patterns of genetic structure within a river system. For example, biased distributions of genetic variation between upstream and downstream populations (i.e., downstream populations harbor higher levels of genetic variation) would be the result of unidirectional seed migration from upstream sources to downstream sink populations (Waser et al, 1982; Akimoto et al, 1998; Gornall et al, 1998). A lack of a relationship between genetic and geographical distances (isolation by distance; IBD) among populations within a river may be another genetic signature of dispersal influenced by water.…”
mentioning
confidence: 99%
“…At one extreme, passive dispersers are influenced by directional dispersing agents such as ocean currents, river currents or prevailing winds (Watkinson 1985;Pulliam 1988;Holt 1996a;Honnay et al 2001). In rivers, the direction of dispersal is predominantly downstream leading to an accumulation of genetic diversity in populations located in the lower reaches of a river-as discovered for fish (HernandezMartich & Smith 1997) and plant species (Friedman & Stein 1980;Gornall et al 1998). Wind is known to be an important factor for sand dune plants (Keddy 1981) and shifts in temperature isotherms induced by climate change may lead to asymmetric dispersal of species towards the poles and higher altitudes (review by Walther et al 2002).…”
Section: Introductionmentioning
confidence: 99%